Transaksi Jual Beli Online dan Keadilan bagi Konsumen Indonesia - Adlan Ali; Emir Zaygh (Majelis: Jurnal Hukum Indonesia, 2025)
The rapid growth of online commerce in Indonesia has significantly transformed the way people fulfill their daily needs by providing easier, faster, and more flexible access to goods and services through digital technology. Despite these advantages, the development of e-commerce also presents serious challenges, including rising cases of online fraud, discrepancies between advertised and delivered products, failed transactions, and personal data breaches that threaten consumer privacy. These issues create imbalances in digital contractual relationships, undermining trust and legal certainty for buyers. This study aims to analyze the implementation of the principle of fairness for consumers in e-commerce practices in Indonesia, while also identifying regulatory weaknesses and existing dispute resolution mechanisms. Using a normative legal research approach supported by case studies, the study examines the effectiveness of relevant legal frameworks, particularly the Consumer Protection Law (UUPK) and the Electronic Information and Transactions Law (UU ITE). The findings reveal that although these regulations provide a legal basis for consumer protection, their implementation remains inadequate. Weak supervision of online business actors, limited accountability of platform providers in ensuring transaction security, and complex, costly compensation procedures continue to hinder consumer rights protection. These conditions highlight the urgent need to strengthen consumer protection systems that are more adaptive, efficient, and oriented toward public interest. The study emphasizes the importance of improving online dispute resolution mechanisms, enhancing transparency and responsibility of digital platforms, and expanding digital literacy among consumers. Such measures are essential to ensure that fairness in e-commerce is not only guaranteed normatively, but also effectively realized in everyday digital transactions.